JUAL BELI DEBU METAL PERSPEKTIF HUKUM EKONOMI SYARI’AH (Studi di Toko Emas Pasar Talang Padang, Kabupaten Tanggamus, Provinsi Lampung) - Khalifatul Azkiya; Jayusman Jayusman (Fakultas Syariah (Syari'ah Faculty ), 2020)
Humans are social creatures who need each other so they can help. One of them is through the trade route which is carried out on the basis of benefit considerations, namely: buying and selling of metal dust. This buying and selling has been going on for a long time in several gold shops in the Talang Padang market, Tanggamus Regency, Lampung Province. Sellers and buyers do not know the gold content in the dust, so it is suspected that there is gharar. Furthermore, we will discuss how the Islamic law review about the practice of buying and selling metal dust in the gold shop, Talang Padang market, Tanggamus Regency, Lampung Province? This discussion concludes that the law of metal dust buying and selling that occurs in the Talang Padang market, Tanggamus Regency, Lampung Province is authentic. Although it is not yet known the amount of gold in the dust which causes one of the requirements of ma'qūd 'alaih not to be fulfilled, this obscurity (gharar) is gharar which is a small quantity that does not cause the seller or buyer to always lose because the seller and the buyer are the same person. have experience and expertise. So the buying and selling of metal dust is a legal buying and selling in Islam